Genetic effects of chemically and biosynthesized titanium dioxide nanoparticles in vitro and in vivo of female rats and their fetuses - Kamal, Zeinab; Said, Alaa H.; Ebnalwaled, A. A.; Rehan, Ibrahim F.; Zigo, František; Farkašová, Zuzana; Allam, Mohammad (Frontiers in Veterinary Science, 2023)
With the increase in nanoparticles (NPs) products on the market, the possibility of animal and human exposure to these materials will increase. The smaller size of NPs facilitates their entrance through placental barriers and allows them to accumulate in embryonic tissue, where they can then be a source of different developmental malformations. Several toxicity studies with chemically synthesized titanium dioxide NPs (CTiO2 NPs) have been recently carried out; although there is insufficient data on exposure to biosynthesized titanium dioxide NPs (BTiO2 NPs) during pregnancy, the study aimed to evaluate the ability of an eco-friendly biosynthesis technique using garlic extract against maternal and fetal genotoxicities, which could result from repeated exposure to TiO2 NPs during gestation days (GD) 6-19. CTiO2 NPs and BTiO2 NPs were given by gavage to pregnant rats at 100 and 300 mg/kg/day concentrations, respectively. Pregnant rats on GD 20 were anesthetized, uterine horns were removed, and then embryotoxicity was performed. The kidneys of the mothers and fetuses in each group were collected and then maintained in frozen condition. Our results showed that garlic extract can be used as a reducing agent for TiO2 NPs formation. Moreover, BTiO2 NPs showed less toxic potential than CTiO2 NPs in HepG2 cells. Both chemically and biosynthesized TiO2 NPs induced genetic variation in the 16S rRNA sequences of mother groups compared to the control group. Moreover, the genetic effects in the 16S rRNA sequence induced by chemically synthesized TiO2 NPs were greater than those of biosynthesized TiO2 NPs. However, there were no differences between the control group and the embryo-treated groups with chemically and biologically synthesized TiO2 NPs.